Comparison of soil-water characteristic curve (SWCC) on unburned and burned soil at varying temperature - Anis Ayesha, Noraini (2016)
Fires can reduce soil infiltration capacity, induce soil water repellency and increase runoff and erosion. This study examines the effect of temperature under natural and laboratory condition of soil samples collected from hillside at Jalan Gambang. The unburned and burned soil sample were obtained from site. In addition, the soil samples under laboratory condition were burned at three temperatures, i.e. 105, 440 and 800°C. Various soil properties were studied, including specific gravity, Atterberg limits, swell index and organic matter content. The soil-water characteristic curve (SWCC) of all soil samples were also determined. The SWCC were established using chilled-mirror dew point technique. Experimental results demonstrated that temperature at 105°C resulted in an increment in liquid limit, plastic limit and SWCC. At 440°C, the liquid limit, organic matter content and SWCC were reduced and the swell index was eliminated. Heating the soil at 800°C completely eliminated the liquid limit, plastic limit, swell potential and organic content of soil tested. The soil suction decrease with increasing temperature. From overall experimental results, the natural burned soil was predicted had experienced a fire at temperature between 105°C to 440°C.